Pomen izobraževanja diplomiranih medicinskih sester v referenčnih ambulantah - Petek Šter, Marija (Obzornik zdravstvene nege, 2015)
Introduction: Graduated nurses are involved in additional educational process to be prepared for working in model practices. The aim of our research was to recognize the necessity for further education and to evaluate the success of additional education for graduated nurses in model practices in the field of arterial hypertension. Methods: The research included 143 graduated nurses who attended a thirty-five hour educational programme on arterial hypertension from January 2012 to March 2013. We assessed the improvement in knowledge of the management of patients with arterial hypertension, the satisfaction of the attendees with the entire educational programme, the particular topics of the module and the teaching methods. We used quantitative (descriptive statistics methods, paired t-test, one sample t-test) and qualitative research methods. Results: In assessing prior knowledge, significant differences were noted between attendees (test results varied from 15.0 % to 100.0 %). The level of knowledge at the end of the educational programme was remarkably higher (56.6 % at the beginning vs. 89.1 % at the end of the educational programme, p < 0.001). Moreover, the satisfaction with the entire educational programme and with its particular modules was high: the mean value on a scale from 5 to 10 was 8.6 (s = 1.3). Teaching methods were assessed as appropriate: the mean value on a scale from 1 to 5 was 4.6 (s = 0.6). Attendees were satisfied with the usefulness and the quality of the lectures, availability of lecturers and the correlation between theory and practice through the use of a casebased discussion. Discussion and conclusion: Our results support the necessity for additional education of graduated nurses working in model practices in the field of arterial hypertension.
Keywords: družinska medicina; education; family medicine; izobraževanje; kakovost; medicinske sestre; needs assessment; ocena potrebe; quality; satisfaction; teamwork; timsko delo; zadovoljstvo